Eliciting Discount Functions when Baseline Consumption changes over Time - Anke Gerber; Kirsten I.M. Rohde (Tinbergen Institute, 2009)
Many empirical studies on intertemporal choice report preference reversals in the sensethat a preference between a small reward to be received soon and a larger reward to bereceived later reverses as both rewards are equally delayed. Such preference reversals arecommonly interpreted as contradicting constant discounting. This interpretation is correctonly if baseline consumption to which the outcomes are added, remains constant over time.The difficulty with measuring discounting when baseline consumption changes over time,is that delaying an outcome has two effects: (1) due to the change in baseline consumption,it changes the extra utility from receiving the outcome, and (2) it changes the factor bywhich this extra utility is discounted. In this paper we propose a way to disentangle thetwo effects, which allows us to draw conclusions about discounting even when baselineconsumption changes over time.
Keywords: D91; D81; 330; Hyperbolic discounting; Constant discounting; Preference reversals; Decreasing impatience; Konsumentenverhalten; Zeitpräferenz; Entscheidung bei Unsicherheit; Theorie